Category shifts in the Chinese–English translation of animal idioms in Journey to the West - Deng, Lulu; Abdullah, Muhammad Alif Redzuan (Academy Publication, 2024)
Idioms are important elements of language and culture, forming the essence of language and the core of vocabulary. Animal idioms naturally have different connotations in the Chinese and Western cultures, which can pose a tremendous challenge for translators. Thus, the reasons for translators’ choices in this context are significant. To better understand this subject, this study investigates the cognitive category shifts in the translations of animal idioms in Journey to the West. Through the theory of cognitive category shifts, the paper finds that translators’ choices are influenced by cognitive concepts derived from their living environments, cultural backgrounds, and knowledge reserves.